2018
DOI: 10.2106/jbjs.17.00154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Intra-Articular Injection of a Microsphere Formulation of Triamcinolone Acetonide on Knee Osteoarthritis Pain

Abstract: Background:Intra-articular corticosteroids relieve osteoarthritis pain, but rapid systemic absorption limits efficacy. FX006, a novel, microsphere-based, extended-release triamcinolone acetonide (TA) formulation, prolongs TA joint residence and reduces systemic exposure compared with standard TA crystalline suspension (TAcs). We assessed symptomatic benefits and safety of FX006 compared with saline-solution placebo and TAcs.Methods:In this Phase-3, multicenter, double-blinded, 24-week study, adults ≥40 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
159
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(177 citation statements)
references
References 33 publications
16
159
1
1
Order By: Relevance
“…The differences in SF TA concentrations observed in this studydGMs of 3590.0 and 290.6 pg/mL at Week 6 and Week 12, respectively, for FX006 and 7.7 pg/mL at Week 6 for TAcsdlikely constitute the basis for pharmacologic differentiation and provide a rational hypothesis for between-treatment efficacy differences observed in Phase 2/3 trials 37,39,47 39 . These effects are clinically important; post-hoc analyses demonstrated that the improvements in all WOMAC subscale scores afforded by FX006 exceeded the minimum clinically important improvement (MCII) thresholds utilized by the American Academy of Orthopedic Surgeons (AAOS) 39e42 .…”
Section: Synovial Concentrations Of Ta E Clinical Implicationsmentioning
confidence: 55%
See 2 more Smart Citations
“…The differences in SF TA concentrations observed in this studydGMs of 3590.0 and 290.6 pg/mL at Week 6 and Week 12, respectively, for FX006 and 7.7 pg/mL at Week 6 for TAcsdlikely constitute the basis for pharmacologic differentiation and provide a rational hypothesis for between-treatment efficacy differences observed in Phase 2/3 trials 37,39,47 39 . These effects are clinically important; post-hoc analyses demonstrated that the improvements in all WOMAC subscale scores afforded by FX006 exceeded the minimum clinically important improvement (MCII) thresholds utilized by the American Academy of Orthopedic Surgeons (AAOS) 39e42 .…”
Section: Synovial Concentrations Of Ta E Clinical Implicationsmentioning
confidence: 55%
“…These effects are clinically important; post-hoc analyses demonstrated that the improvements in all WOMAC subscale scores afforded by FX006 exceeded the minimum clinically important improvement (MCII) thresholds utilized by the American Academy of Orthopedic Surgeons (AAOS) 39e42 . Specifically, FX006 effects achieved the AAOS definition of 'clinically significant' at Weeks 4 and 8 and 'possibly clinically significant' at Week 12 for all WOMAC subscale scores 39,40 . Conversely, TAcs never achieved the AAOS definition of 'clinically significant' at any time point for any WOMAC subscale 39,40 .…”
Section: Synovial Concentrations Of Ta E Clinical Implicationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Despite the fact that standard IA steroids can reliably reduce pain only for 1e3 weeks 12 , it is still the only IA injection therapeutics recommended by treatment guidelines 9,10 , and its chronic use may be associated with cartilage damage 41 . More recently, a novel, microsphere-based, extended-release steroid formulation showed a prolonged pain relief for 12 weeks following a single IA injection in study participants with painful knee OA 42 and it is currently indicated for single use. So, there is an urgent need for effective and safe alternative IA injection treatments to fill in the chronic journey of OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Por otra parte, las causas de dolor sinovial ocurren como consecuencia de la irritación de las terminaciones nerviosas sensoriales dentro de la capa sinovial, que cubre los osteofitos y la propia inflamación del tejido sinovial por prostaglandinas, leucotrienos y citocinas, que estimulan los nociceptores, además de la distención articular y el edema. [19][20][21] El dolor de la artrosis de rodilla también es de origen muscular, a través de la inestabilidad articular típica de esos enfermos, aumenta el estrés sobre la articulación y por ende la activación de los nociceptores.…”
Section: Características Generales Del Dolor En La Artrosis De Rodillaunclassified